(3GdJcedI dcJGH GdUdIs - (3GHf GdGHGQ , CHh YHO Gddg eMeO Hf YHO Gddg Hf CHj HcQ GdbVGYj GdHdfSj, GHf GdGHGQ,J (B658 (3g` s
(3ChdgG (B:s
(3jHOC HJQLeI YHO GdQMef Hf TeGSI Hf PjH s
(3BNQgG (B:s
(3jfJgi CKfGA JQLeI eSYOI HfJ CHj GdMSf Ydi Hf CMeO Hf GdHGPT s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B233 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B204s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdJGQjNs